A novel approach to the prediction of long-term creep fracture: with application to 18Cr–12Ni–Mo steel (plate and bar) - Mark Evans (Journal of Materials Science, 2009)
Designers of new power-generation plants are looking to make use of new and existing high-strength austenitic steels so that these plants can operate with much higher steam and therefore metal temperatures. However, this article shows that the recently developed Wilshire–Scharning methodology is incapable of producing accurate long-term life predictions of these materials from short-term data. This article puts forward a modification of this approach that should enable existing and newly developed austenitic stainless steels to be brought into safe operation more cost effectively and over a quicker time span. Estimation of this model showed that the activation energy for creep was dependent on whether the test stress was above or below the yield stress. Analysis of the results from tests lasting only up to 5,000 h accurately predict the creep lives for stress–temperature conditions causing failure in 100,000 h or more.